Prevalence and burden of asthma in five European countries: a retrospective cross-sectional study - Juan Wisnivesky; Asif H. Khan; Imène Gouia; Juby Jacob-Nara; Siddhesh Kamat; Dena Jaffe; deMauri Mackie; Bridget L. Balkaran (BMJ Open)
Objective To evaluate the burden of asthma in five European countries (5EU; France, Germany, Italy, Spain and United Kingdom [UK]).Design A retrospective cross-sectional study was conducted based on the data from the 2018 National Health and Wellness Survey. Health-related quality of life (HRQoL), work productivity and activity impairment, and healthcare resource utilisation (HCRU) were compared between different groups: asthma versus non-asthma, mild/moderate/severe asthma versus non-asthma and moderate/severe asthma versus mild asthma.Settings Internet-based survey across Western Europe.Participants Adult patients (aged ≥18 years) with self-reported physician diagnosis of asthma and experienced asthma symptoms in the past 12 months.Outcome measures Socio-demographic characteristics, asthma-related outcomes, HRQoL and productivity, HCRU and prevalence of asthma.Results The prevalence of asthma in the 5EU was 6.7% (95% CI: 6.5% to 6.9%), with the UK reporting the highest rates (10.4%; 95% CI: 9.9% to 10.9%). About 52.0% of the respondents had mild asthma, 27.9% had moderate and 20.1% had severe asthma. The asthma group reported significantly poorer HRQoL, higher rates of overall work productivity impairment and activity impairment, and a greater number of visits to emergency room, healthcare provider and hospitalisations versus the non-asthma group (all p<0.001). Similar trend was observed for all outcomes among respondents with moderate or severe versus mild asthma.Conclusion Asthma prevalence and burden are still high in Western Europe, indicating the need for effective interventions that could lead to improved outcomes.